Biological approach for management of anterior tooth trauma: Triple case report - Puneet Goenka; Samir Dutta; Nikhil Marwah (Wolters Kluwer Medknow Publications, 2011)
Anterior crown fractures are a common form of injury that mainly affect children and adolescents. The position of maxillary incisors and their eruptive pattern carries a significant risk for trauma. In the pre-adhesive era, fractured teeth needed to be restored either with pin-retained inlays or cast restorations that sacrificed healthy tooth structure, and were a challenge for clinicians to match with adjacent teeth. The development of adhesive dentistry has allowed dentists to use the patient's own fragment to restore the fractured tooth. Three cases are presented here with complicated crown fracture of maxillary central incisors; the reattachment of the fractured tooth segment in these cases has been performed using different combinations of techniques, viz. simple reattachment, circumferential bevel and internal dentinal groove.